(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Abstract In cities all around the world, air pollution is a major issue that is typically brought on by particulate matter, such as dust, smoke, pollen, bacteria, etc. The problem is that some of these are able to get inside our homes, especially if we live in a large city. The Wi-Fi Robotic Vacuum Cleaner and Air Purifier with Automatic/Manual Control Operation is a two-in-one device, a vacuum cleaner, and an air purifier integrated with sensors for effective functionality. It sucks in small particles of dry dirt on smooth floor surfaces and purifies air against fine and harmful particles in the air. The results of functional testing for the components and sensors used in the prototype showed the in-depth details of the prototype’s design, program, and electric circuit connection. The testing showed that the obstacle sensors, gas sensors, and fine dust sensors serve their functions. The filters on the vacuum and air purifier also showed physical evidence of catching small particles, which supports the fact that the prototype is able to collect small particles of dirt both on the floor and in the air. By means of prototype testing and data analysis, the researchers found out that moving an air purifier together with a vacuum cleaner gives us the ideal robot for indoor hygiene, improving not only the air quality but also removing dust from the floor. The robot is also portable and easy to control for manual navigation.